2015
DOI: 10.1007/s11205-015-1199-8
|View full text |Cite
|
Sign up to set email alerts
|

International Migration, Remittances Inflow and Household Welfare: An Intra Village Comparison from Pakistan

Abstract: This study explores the financial costs, time involved in migration and benefits at household level. A household survey has been conducted to investigate about characteristics of migrants, transaction costs and sources of financing by which overseas migration is financed. Results of PSM technique explored that overseas migration conveys worthwhile benefits as measured by their total expenditures, food expenditures, non-food expenditures, clothing expenditures, expenditures on pots and pans, expenditures on veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
4
8
0
Order By: Relevance
“…Besides reducing poverty, international remittances enhance the welfare of remittance recipient households. Some previous studies have found a positive relation between remittances and welfare [15,20,[28][29][30]. They found that remittance recipient households spend most amount of remittance received on consumption purposes.…”
Section: Source: World Development Indicatormentioning
confidence: 92%
“…Besides reducing poverty, international remittances enhance the welfare of remittance recipient households. Some previous studies have found a positive relation between remittances and welfare [15,20,[28][29][30]. They found that remittance recipient households spend most amount of remittance received on consumption purposes.…”
Section: Source: World Development Indicatormentioning
confidence: 92%
“…Cuong and Linh [ 8 ] reported that international remittances increase per capita income and per capita expenditure of the household in Vietnam while it reduces employment of remaining members. Javed, Awan, and Waqas [ 9 ] showed that international migration delivers benefits as an increase in various forms of household expenditures in Pakistan. Wadood and Hossain [ 10 ] reported the remittance-receiving households are better off in terms of consumption expenditure compared to non-receiving ones in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, our dataset is longitudinal, which allows us to take an empirical approach to establish a relationship between remittances and household welfare in a more rigorous way, since longitudinal data enables us to correct unobserved factors and address endogeneity using exogenous shocks to households. There have been a variety of studies reporting the positive impact of remittances on household welfare in Vietnam [ 7 , 8 ], Pakistan [ 9 ], Bangladesh [ 10 ], Kenya [ 11 ], Malawi [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Cuong (2008) found an opposite direction: the impact of international remittances on income is greater than consumption expenditures, meaning that a large proportion of international remittances are used for savings and investment purposes. Javed et al (2017) found that the effect of international remittance on food security is greater than on wealth.…”
Section: Key Findings Of Previous Literaturementioning
confidence: 99%